Mobile Phones and Mozambique Traders: What is the Size of Reduced Search Costs and Who Benefits? - Wouter Zant (Tinbergen Institute, 2019)
We investigate to what extent the roll-out of the mobile phone network in Mozambique reduced transport costs and search costs, and thereby decreased spatial price dispersion and improved market efficiency. Estimations are based on data of transport costs of maize grain and maize market prices. The mobile phone rollout explains a 10%-13% reduction in maize price dispersion. Around half of this reduction is associated with search costs related to transport, the other half with other search costs, for example for the collection of maize in source markets. Search costs are substantial and also a substantial component of total transport costs. Benefits of increased market efficiency are biased towards consumer markets. Results are robust for non-random rollout of the mobile phone network and several other threats.
Keywords: Q13; O13; O33; Q11; 330; search costs; transport costs; mobile phones; agricultural markets; maize prices; Mozambique; sub-Sahara Africa